Legal Responsibilities For The Insured Resulting From Delay In Insurance Broker Premium Deposit To The Insurer In The Insurance Agreement - Tasman (Master of Law Program, Ekasakti University, 2025)
The provisions for premium payments from insurance brokers to insurers are regulated in applicable laws and regulations. The provisions for insurance brokers to pay premiums to insurers are regulated by Financial Services Authority Regulation Number 70 of 2016 concerning the Implementation of Insurance Brokerage Companies, Reinsurance Brokerage Companies, and Insurance Loss Assessment Companies. The role of Insurance Brokers is quite important for the insured to be able to assist in paying premiums to insurers based on the regulated provisions. This is because insurance premiums in an insurance company are a company necessity in increasing company profits and can cover claims filed by the insured. However, there are problems in the field where late premium payments occur which are not the fault of the insured but rather the fault of the insurance broker who is late and will cause losses to the insured. In this case, the insured has legal remedies so that they can be given a good solution. This research is a legal research with a statute approach and an analytical approach. The results of this study explain that first, the legal efforts made by the insured regarding the dispute between the Insurance Broker and the Insurance Company (Insurer) are a result of the negligence of the insurance broker who did not pay the insured's policy premium. In fact, the insured considers that the Insurance Broker has carried out manipulative information actions as if there was no problem and finally the Policy was canceled unilaterally by the insurer. Second, the Insured did not clearly see the existing facts, especially the unilateral cancellation of the policy by the insurer that it is mandatory to be notified of the reasons for the cancellation. Thus, the insured's legal efforts through the criminal realm are only based on Article 31 paragraph (2) Jo. Article 75 of Law Number 40 of 2014 concerning Insurance. The recommendation is, it would be more appropriate for the appropriate legal efforts chosen by the Insured to be carried out through the Non-Litigation Path. Such as a special insurance dispute resolution forum through the Indonesian Insurance Arbitration Mediation Board (BMAI) which has been mandated through the Financial Services Authority Regulation Number. This aims to prove the alleged actions of the Insurance Broker who has been late in paying premiums due to his negligence to the Insurer. In this way, it will be more effective and independent in resolving civil disputes in the insurance industry.